2013
DOI: 10.1590/s1516-35982013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Meat characteristics of Nellore steers fed whole cottonseed

Abstract: -The objective of this study was to evaluate the effect of addition of different levels of cottonseed (0, 14.35, 27.51 and 34.09 kg/100 kg) in the diet of Nellore steers on the meat characteristics. Thirty-six steers (average initial body weight of 333.50 and average age of 20 months) were kept in feedlot stalls for 94 days, each stall with three animals. The experiment was a completely randomized design with four treatments and nine replications. The values of protein, fixed mineral residue, shear force, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 38 publications
13
28
1
Order By: Relevance
“…The observed higher values of C18:0 in the meat of the animals that were fed 11.50% CS in the diet were closer to those reported by Costa et al (2013), who used 14.35% CS in the feed of the animals. Stearic acid, when consumed by humans, is absorbed in the intestines and transported to the liver by chylomicrons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The observed higher values of C18:0 in the meat of the animals that were fed 11.50% CS in the diet were closer to those reported by Costa et al (2013), who used 14.35% CS in the feed of the animals. Stearic acid, when consumed by humans, is absorbed in the intestines and transported to the liver by chylomicrons.…”
Section: Discussionsupporting
confidence: 88%
“…While Costa et al (2013) observed a linear decrease in EE of the muscle with the addition of CS to the diets of Nellore cattle, a positive correlation between the treatment was found in the present study on protected lipid and intramuscular fat. This finding shows greater efficiency of PL in the passage through the rumen towards the abomasum.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This effect is undesirable because oleic acid intake contributes to increase plasma high-density lipoprotein (HDL) and decrease LDL and triglyceride concentrations in human blood (Gilmore et al, 2011). Costa et al (2013) observed a similar result for oleic acid concentration in meat as a function of different cottonseed levels in the diet (0%, 14%, 27% and 34%). In addition, greater NDF content in the cottonseed diets may have contributed to increase retention time of digesta in the rumen, where UFA were exposed to ruminal biohydrogenation for a longer time.…”
Section: Resultsmentioning
confidence: 86%
“…The high energy content of this oilseed can change ruminal fermentation by suppressing bacterial cellulolytic and methanogenic activity (Van Soest, 1994). Problems in beef flavor have been associated with the use of cottonseed (Costa et al, 2013). Given that cottonseed diets may compromise meat quality, it is critical to determine feed cottonseed and gossypol contents that will not change meat characteristics.…”
Section: Introductionmentioning
confidence: 99%